Structure, microstructure and magnetic properties study of ceramic composite (La0.67Ca0.33MnO3)1-x/(Nano-sizedα-Fe2O3)x - Wan Jusoh, W. N. W.; Lim, K. P.; Awang Kechik, M. M.; Halim, S. A.; Ng, S. W. (Faculty of Science, Universiti Putra Malaysia, 2015)
The structural, microstructure and magnetic properties of polycrystalline (La0.67Ca0.33MnO3)1-x/(α-Fe2O3)x composites where x = 0%, 5%, 10%, 15%, 20% were investigated. Polycrystalline La0.67Ca0.33MnO3 (LCMO) was synthesized via solid state reaction at high sintering temperature while for nano-sized Fe2O3 (20-50 nm) a commercial product was used. X-ray diffraction (XRD) patterns show that parent compound of La0.67Ca0.33MnO3 is a single phase without any detectable impurity and give orthorhombic structure with space group Pbnm (62) while α- Fe2O3 is in cubic form with space group I a -3 (206). As Fe2O3 content x increases, the magnetization M values decrease as observed via Vibrating Sample Magnetometer (VSM) at room temperature. Higher magnetization is noticed inpure LCMO rather than in LCMO composites added with α- Fe2O3. However, Scanning Electron Microscopy (SEM) shows that nano-sized Fe2O3 mainly distributed at the grain boundary of La0.67Ca0.33MnO3. The particle size of LCMO composites shows fluctuation; meanwhile particle size of α- Fe2O3 shows almost similar values except for sample with the addition of 15% of α- Fe2O3 where lowest particle size with higher coercivity and retentivity are observed. As compared to pure La0.67Ca0.33MnO3, Fe2O3 doping level at the grain boundaries can be assumed to modify the magnetic properties of La0.67Ca0.33MnO3.